Determination of Diazinon Residue Used in Shallot against Armyworm (Spodoptera exigua) - Isam Eldeen Ibrahim Hassan Abdalla; Edhi Martono; Christanti Sumardiyono (Universitas Gadjah Mada, 2008)
The research was carried out to identify the residue of diazinon in shallot crop which was grown inYogyakarta Special Territory, Bantul Regency (Parangtritis, Samas and Sanden). Questionnaires were also distributed to farmers in the area to find out the background of diazinon application. Samples were taken from these locations and Bantul market, and were analyzed using Thin Layer and Gas Chromatography (TLC and GC) methods. TLC technique detected diazinon residues in all samples except Parangtritis sample from farmers plot with no diazinon spraying. GC results showed that all the samples diazinon residues were well below maximum residue limit (MRL). The least residue level (0.0029 ppm) was detected in one week after harvesting sample from Sanden. The highest residue level (0.0231 ppm) was detected in the harvesting time sample from Parangtritis.